Preliminary Study of Sonication Time for Extracting Natural Dye and Antioxidant from Sargassum duplicatum - Ummi Roudhoh; Romadhon Romadhon; Ahmad Suhaeli Fahmi (agriTECH, 2023)
Sargassum duplicatum is a brown seaweed containing various chemical compounds with potential applications as a natural dye and antioxidant. These compounds include alginate, protein, vitamin C, tannins, iodine, phenols, and pigments such as chlorophyll a, chlorophyll c, fucoxanthin, xanthophyll, and carotene. Therefore, this study aimed to determine the effect of varying extraction times on the color and antioxidant quality of Sargassum duplicatum extract. One of the methods used to extract Sargassum duplicatum is ultrasonication, which involves using ultrasonic waves to break down the cell walls of the material and facilitate efficient compound extraction. The extraction was carried out at 15 (A), 30 (B), and 45 minutes (C), with three repetitions for each treatment. The assessed parameters included yield calculation, total carotenoids, antioxidant activity, and color intensity. Parametric data were analyzed using ANOVA and Tukey HSD follow-up tests. The extraction process used an 80% ethanol solvent at 40 °C and a frequency of 42 kHz. This study employed an experimental laboratory approach using a completely randomized design (CRD) with different extraction times. The results showed significant differences (p<5%) in yield value, total carotenoids, antioxidant activity, and color intensity of Sargassum duplicatum extract at different extraction times. The best results were obtained at 45 minutes, yielding 86.66%, with 9.62% total carotenoids, an IC50 value of 1241.02 ppm, and lightness (L*), redness (a*), and yellowness (b*) values of 4.44, -3.46, and 37.90, respectively.